PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE LEARNING CELL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 LEMBAH GUMANTI - Wulandari, Fitri; Rismen, Sefna; Suryani, Mulia (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was conducted based on the phenomena showing that the students were not accustomed to discuss in pairs. This research was aimed at revealing whether the mathematics conceptual understanding of the students taught by using The Learning Cell active learning strategy was better than that of students taught by using the conventional one in class VIII of SMPN 4 Lembah Gumanti. This was an experimental research which used random toward the subject design. Populasion were students of SMPN 4 Lembah Gumanti which consists of three classes. Samples were taken at random that was selected as the experimental class VIIIB and as control class VIIIA. The instrument of the research was an essay post-test whose reliability was 0.65. Based on the result of data analysis by using t-test assisted with software MINITAB, it was found that P-value was 0.022 which was smaller than Î± value. This result signified that H0 was rejected. Thus, it was concluded that the mathematics conceptual understanding of the students taught by using The Learning Cell active learning strategy was better than that of students taught by using conventional learning on 95% of reliability level.